The stirling alternative power systems, refrigerants and heat pumps - Walker, Graham; Reader, Graham; Fauvel, Owen R.; Bingham, Edward R. (Gordon and Breach Science Pub. Switzerland, 1994)
Provides an up-to-date reference on the technology, history, and practical applications of Stirling engines, including recent developments in the field and a convenient survey of literature on the Stirling engine.
Keywords: Stirling engines; Refrigeration and refrigerating machinery; Heat pumps